Space Flight - Dekoulis, George (IntechOpen, 2018)
Space has always been intriguing people's imagination. However, space flight has only been feasible over the last 60 years. The collective effort of distinguished international researchers, within the field of space flight, has been incorporated into this book suitable to the broader audience. The book has been edited by Prof. George Dekoulis, Aerospace Engineering Institute (AEI), Cyprus, an expert on the state-of-the-art implementations of reconfigurable space physics systems. The book consists of six sections, namely, "Introduction," "Spacecraft Simulators," "Spacecraft Navigation," "Spacecraft Propulsion," "Suborbital Flight," and "Deep-Space Flight." We hope that this book will be beneficial for professionals, researchers, and academicians and inspires the younger generations into pursuing relevant academic studies and professional careers within the space industry.